Source analysis of the tropospheric NO2 based on MAX-DOAS measurements in northeastern China. (1st August 2022) - Liu, Feng; Xing, Chengzhi; Su, Pinjie; Luo, Yifu; Zhao, Ting; Xue, Jiexiao; Zhang, Guohui; Qin, Sida; Song, Youtao; Bu, Naishun
Abstract: Ground-based Multi-Axis Differential Optical Absorption Spectroscopy (Max-DOAS) measurements of nitrogen dioxide (NO2 ) were continuously obtained from January to November 2019 in northeastern China (NEC). Seasonal variations in the mean NO2 vertical column densities (VCDs) were apparent, with a maximum of 2.9 × 10 16 molecules cm −2 in the winter due to enhanced NO2 emissions from coal-fired winter heating, a longer photochemical lifetime and atmospheric transport. Daily maximum and minimum NO2 VCDs were observed, independent of the season, at around 11:00 and 13:00 local time, respectively, and the most obvious increases and decreases occurred in the winter and autumn, respectively. The mean diurnal NO2 VCDs at 11:00 increased to at 08:00 by 1.6, 5.8, and 6.7 × 10 15 molecules cm −2 in the summer, autumn and winter, respectively, due to increased NO2 emissions, and then decreased by 2.8, 4.2, and 5.1 × 10 15 molecules cm −2 at 13:00 in the spring, summer, and autumn, respectively. This was due to strong solar radiation and increased planetary boundary layer height. There was no obvious weekend effect, and the NO2 VCDs only decreased by about 10% on the weekends. We evaluated the contributions of emissions and transport in the different seasons to the NO2 VCDs using a generalized additive model, where the contributions of local emissions to the total in the spring, summer, autumn, and winter were 89 ± 12%, 92 ± 11%, 86 ± 12%, and 72 ± 16%, respectively. The contribution of regional transport reached 26% in the winter, and this high contribution value was mainly correlated with the northeast wind, which was due to the transport channel of air pollutants along the Changbai Mountains in NEC. The NO2 /SO2 ratio was used to identify NO2 from industrial sources and vehicle exhaust. The contribution of industrial NO2 VCD sources was >66.3 ± 16% in Shenyang due to the large amount of coal combustion from heavy industrial activity, which emitted large amounts of NO2 . Our results suggest that air quality management in Shenyang should consider reductions in local NO2 emissions from industrial sources along with regional cooperative control. Graphical abstract: Image 1 Highlights: NO2 vertical column densities (VCDs) peaked in winter due to enhanced heating emissions. NO2 VCDs showed an uptrend from 08:00 to 11:00 and had a slight decrease at noon. NO2 was mainly sourced from local industrial NO2 emissions in Shenyang. Regional transport from the northeastern direction contributed 26% to NO2 in winter.